The Individualistic Principles Of Thiru Muthuramalinga Thevar (Journal of Namibian Studies : History Politics Culture, 2023)
Muthuramalinga Thevar was an outstanding son of Mother India. A versatile personality Freedom fighter, Political activist, Parliamentarian, Social and Religious reformer, Trade union leader and Orator. His Nationalism was an article of faith. He was a model for many human being. He was an embodiment of virtue, service, truth, sacrifice, wisdom, courage, charity and nobility. He believed in morality, equality, justice, love and service to God. He shaped his character and personality, honesty and braveness and molded him as a social reformer. By their Individualistic traits and calibre, they attained an enhanced his status.